2022
DOI: 10.3390/cancers14184498
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Molecular Subgroups in Esophageal Adenocarcinoma to Predict Response to Neo-Adjuvant Therapies

Abstract: Esophageal adenocarcinoma (EAC) is a highly aggressive cancer and its response to chemo- and radiotherapy is unpredictable. EACs are highly heterogeneous at the molecular level. The aim of this study was to perform gene expression analysis of EACs to identify distinct molecular subgroups and to investigate expression signatures in relation to treatment response. In this prospective observational study, RNA sequencing was performed on pre-treatment endoscopic EAC biopsies from a discovery cohort included betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In this study, 71 out of 72 EAC cases were identified to have CIN indicating similarities between EAC and gastric cancers with CIN [1]. More recently, our research group was able to further differentiate EAC into three molecular subgroups, characterized by (i) p38 MAPK/Toll-like receptor signaling, (ii) an activated immune system and (iii) impaired cell adhesion, and this classification was associated with response to neo-adjuvant treatment [143].…”
Section: Geneticsmentioning
confidence: 66%
See 2 more Smart Citations
“…In this study, 71 out of 72 EAC cases were identified to have CIN indicating similarities between EAC and gastric cancers with CIN [1]. More recently, our research group was able to further differentiate EAC into three molecular subgroups, characterized by (i) p38 MAPK/Toll-like receptor signaling, (ii) an activated immune system and (iii) impaired cell adhesion, and this classification was associated with response to neo-adjuvant treatment [143].…”
Section: Geneticsmentioning
confidence: 66%
“…In different studies, it has been demonstrated that EAC can be divided into various molecular subgroups. One subclassification of EAC can be used to predict response to neoadjuvant treatment for EAC patients [143]. However, the subclassifications in several studies seem to have less clinical significance [108,123].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In EAC, M2 macrophage polarization appears to occur in response to tumor upregulation of Th2 pathways, leading to increased IL-4 and IL-13 [ 82 ]. Like other cancers, EAC treatment success is partially dictated by relatively low levels of infiltrating macrophages compared to other immune constituents [ 83 ]. Taken together, M2 macrophages may become an attractive target in the emerging treatment of EAC.…”
Section: Discussionmentioning
confidence: 99%